A Home-Based Individual Cognitive Stimulation Program for Older Adults With Cognitive Impairment: A Randomized Controlled Trial - Silva, Rosa; Bobrowicz-Campos, Elzbieta; Santos-Costa, Paulo; Cruz, Ana Rita; Apóstolo, João (Frontiers in Psychology, 2021)
Objective: This study aims to assess the feasibility and meaningfulness of a home-based individual cognitive stimulation (iCS) program delivered by caregivers to persons with cognitive impairment (PwCIs). It also aims to assess whether the older adults receiving this program improved their cognitive, neuropsychiatric, and depressive symptoms and quality of life and whether their caregivers improved their mental and physical health. Methods: A randomized controlled trial was conducted with PwCI-caregiver dyads recruited from the community. Participants were allocated to two groups: intervention (n = 28) and control (n = 24). The intervention group received the European Portuguese version of the Individual Cognitive Stimulation Program - Making a Difference 3 (MD3-P). The control group received usual care. The iCS therapy program was implemented three times a week for 12 weeks. Caregivers were supported by the researchers to deliver the sessions at home. Participants were assessed at baseline and at the end of the intervention (week 13). Feasibility and meaningfulness were assessed through the attrition rate, adherence, and degree of satisfaction with the sessions. Four interviews were conducted (after week 13) to understand participants’ experiences. Results: The attrition rate was 23.1%. The dyads reported that they did not have high expectations about the iCS program before starting the study. Nevertheless, as the program evolved, caregivers noted that their family members had improved some areas of functioning. Intention-to-treat analysis based on group differences revealed a significant improvement in PwCIs’ cognition, specifically in their orientation and ability to follow commands. The intervention had no impact on other variables such as caregivers’ physical and mental health. Conclusion: The iCS program implemented by caregivers showed promising results in improving PwCIs’ cognition. The participants who completed the intervention attributed a positive meaning to the MD3-P, confirming it as a valid non-pharmacological therapeutic approach to reducing frailty in PwCIs in community settings.